2010
DOI: 10.1158/0008-5472.can-10-2333
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase-Dependent Oncolytic Adenovirus Sensitizes Human Cancer Cells to Ionizing Radiation via Inhibition of DNA Repair Machinery

Abstract: The inability to repair DNA double-strand breaks (DSB) leads to radiosensitization, such that ionizing radiation combined with molecular inhibition of cellular DSB processing may greatly affect treatment of human cancer. As a variety of viral products interact with the DNA repair machinery, oncolytic virotherapy may improve the therapeutic window of conventional radiotherapy. Here, we describe the mechanistic basis for synergy of irradiation and OBP-301 (Telomelysin), an attenuated type-5 adenovirus with oncol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 39 publications
2
54
0
Order By: Relevance
“…During the infection with the telomerase-driven oncolytic adenovirus OBP301, the degradation of MRN complex was accompanied by greatly reduced levels of ATM activation (Kuroda et al 2010). It is possible that dl922-947 infection is not able to fully suppress the early events in DNA damage signaling, as MRN complex degradation may not in itself be sufficient to preclude/ reduce ATM and ATR kinase activation, as previously reported (Nichols et al 2009).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…During the infection with the telomerase-driven oncolytic adenovirus OBP301, the degradation of MRN complex was accompanied by greatly reduced levels of ATM activation (Kuroda et al 2010). It is possible that dl922-947 infection is not able to fully suppress the early events in DNA damage signaling, as MRN complex degradation may not in itself be sufficient to preclude/ reduce ATM and ATR kinase activation, as previously reported (Nichols et al 2009).…”
Section: Discussionmentioning
confidence: 64%
“…In a study using a telomerase-specific replication selective adenovirus (OBP-301), viral infection was shown to result in radiosensitivity in A459 small-cell lung cancer cells (Kuroda et al 2010). In the same study, a dose-dependent increase in adenoviral uptake and coxsackie adenovirus receptor expression was also observed.…”
Section: Discussionmentioning
confidence: 99%
“…27 We previously reported that OBP-301 enhances radiosensitization in human cancer cells by inhibition of the DNA repair machinery. 28 Based on these findings, combination therapy with OBP-301, VPA and radiation is an exceedingly promising antitumor therapy.…”
mentioning
confidence: 99%
“…The MRN complex is a conserved protein complex that plays a key role in the response to DNA damage (19). Kuroda1 et al (20) demonstrated that degradation of MRN complex results in the inability to repair DNA double-strand breaks (DSB) and leads to radiosensitization, which indicates that RAD50 plays a key role in radioresistance.…”
Section: A B C D E F Discussionmentioning
confidence: 99%